Effect of Different Treatments During Synthesis on Physical and Chemical Properties of Bacterial Cellulose/Chitosan Composite Film - Izzaty, Annisa Nabila; Yuanita, Emmy; Sudirman, Sudirman; Sarkono, Sarkono; Al Faris, Muhammad; Ulfa, Maria (The Journal of Pure and Applied Chemistry Research, 2024)
Bacterial cellulose (BC) and chitosan (Chi) are biopolymers that play a vital role in various industrial applications due to their unique properties, such as biodegradability, biocompatibility, flexibility, and excellent physical properties. Combined, these two materials can create composites with exceptional characteristics, which can be tailored for specific applications. This study aimed to evaluate the effect of different ultrasonication and stirring treatments on the synthesis of BC/Chi composites, focusing on their chemical, physical, and mechanical properties. Based on the results of microscopy, SEM-EDS, and FTIR analysis, it was found that ultrasonication treatment provides a more effective dispersion process, resulting in higher physical and mechanical properties than BC/Chi stirring.